Analisa Pengaruh Pergantian kWh Meter Lama Pascabayar ke kWh Meter Baru Pascabayar terhadap kWh Jual di ULP Talang Padang - L Tobing, Willy Pranata; Bandri, Sepannur; Putra, Andi Muhammad Nur; Zulkarnain, Zulkarnain; Rachman, Arfita Yuana Dewi (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The purpose of this study was to analyze the effect of replacing old postpaid kWh meters with new postpaid kWh meters on kWh sales at ULP Talang Padang. The research methods included comparative analysis of old and new meter reading data, manual measurement of electrical parameters (voltage, current, power factor), and statistical tests of measurement errors. The results showed that meter replacement significantly improved recording accuracy, meaning that replacing new kWh meters was effective in reducing energy losses and increasing PLN's revenue.